2021
DOI: 10.1175/jcli-d-20-0138.1
|View full text |Cite
|
Sign up to set email alerts
|

How Reliable Are Decadal Climate Predictions of Near-Surface Air Temperature?

Abstract: Decadal climate predictions are being increasingly used by stakeholders interested in the evolution of climate over the coming decade. However, investigating the added-value of those initialised decadal predictions over other sources of information typically used by stakeholders generally relies on forecast accuracy, while probabilistic aspects, although crucial to users, are often overlooked. In this study, the quality of the near-surface air temperature from initialised predictions has been assessed in terms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 65 publications
(83 reference statements)
3
7
0
Order By: Relevance
“…Results for the MME indicate a reliable ensemble over most of the globe and especially over large areas of the tropical Pacific Ocean up to the third winter. These findings are in agreement with previous studies that have demonstrated the improved reliability of multimodel compared to SMEs (Doblas‐Reyes et al., 2009; Palmer et al., 2004; Stockdale et al., 2009; Verfaillie et al., 2020; Weisheimer et al., 2009). To compare the level of reliability of all three ensembles quantitatively, we analyzed a number of grid cells which are significantly unreliable over the tropical band (20°N–20°S) (Table ).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Results for the MME indicate a reliable ensemble over most of the globe and especially over large areas of the tropical Pacific Ocean up to the third winter. These findings are in agreement with previous studies that have demonstrated the improved reliability of multimodel compared to SMEs (Doblas‐Reyes et al., 2009; Palmer et al., 2004; Stockdale et al., 2009; Verfaillie et al., 2020; Weisheimer et al., 2009). To compare the level of reliability of all three ensembles quantitatively, we analyzed a number of grid cells which are significantly unreliable over the tropical band (20°N–20°S) (Table ).…”
Section: Resultssupporting
confidence: 93%
“…In particular, it was demonstrated for seasonal forecasts that a fixed‐size ensemble constructed from different models is more reliable than an ensemble of the same size from a single model (Palmer et al., 2004; Stockdale et al., 2009; Weisheimer et al., 2009). Similar results comparing MMEs versus single‐model ensembles (SMEs) were recently found for climate predictions and projections on decadal time scales (Verfaillie et al., 2020).…”
Section: Introductionsupporting
confidence: 81%
“…2.2.1) (Meehl et al, 2021). A better understanding of the three aspects -initialization, model dynamics and forcing responses -is fundamental for better exploiting the climate predictive potential and improving estimates of climate predictability (Keenlyside and Ba, 2010;Cassou et al, 2018;Verfaillie et al, 2021). The existing climate prediction systems undersample effects of model and initialization uncertainty and are not necessarily well suited to address questions related to changes in the observing system.…”
Section: Introductionmentioning
confidence: 99%
“…6). This function can be used to quickly compare modes of variability, skill metrics, differences between methods, or forecast systems as a function of the lead times or seasons (Torralba, 2019;Verfaillie et al, 2021;Lledó and Doblas-Reyes, 2020).…”
Section: Visualizationmentioning
confidence: 99%